Literary Invention and Critical Fashion: Missing the Boat in the Sea of Lentils - Elzbieta Sklodowska (Studies in 20th & 21st Century Literature, 1995)
In pursuing the relation of Sea of Lentils (1979) to the Spanish American literary canon, I argue that while Benítez-Rojo's novel did not fall into the category of the already canonized—and therefore was spared a parricidal gesture of the Post-Boom writers—neither did it belong amidst the previously marginalized texts. I suggest that Sea of Lentils concentrates its internal critique of language and representation around the process of remembering in a manner that is radically at odds not only with the "traditional" historical novel, but with the official voice of the ascendant testimonio as well. Moreover, the notion of memory as unpredictable "turbulent flow" and the breaking down of a globalizing grand récit into "fractal" petites histoires lead us toward chaos theory and Postmodernism. I conclude that while Sea of Lentils prefigured a variety of concerns that were to become dominant in the 1980s, it essentially failed to satisfy the more immediate expectations of invention on the part of "technocratic" critics, on one hand, and, on the other, of "culturalists" longing for a genuinely Latin American and "authentic" discourse.
Keywords: Sea of Lentils; Benítez-Rojo; Post-Boom; critique of language; memory; postmodernism; récit; petites histoires; technocratics; culturalists; discourse; novel; Cuban literature